A Method for Examining Geographic Variation When Denominators Are Unknown, Populations Vary, and Time is of the Essence: Back Surgery as an Example. Issue 24 (15th December 2020) - Weeks, William B.; Weinstein, James N.
Abstract : N/A: Level of Evidence: 3